Study of Gender in Pashto Grammar - Ajmal Khkalay; Shafiqullah Amirzay (RIRAI Publisher, 2023)
According to female perspective the male mentality about them in culture, is the mentality based on narcissism, which is a social reality. On this basis, we can also study languages that, according to women perspective or feminist theory, retain their gender and differentiate between word meanings and grammatical rules based on gender. In these languages, there used to be Avestian and Persian, which now leaves behind gender in the language. now it is Pashto, which still retains gender and differentiates linguistic rules and trends based on gender. In Pashto, gender is dominated by two areas: One in independent concepts and the other in grammatical variations. In Pashto, there is a gender difference in the price of nouns, adjectives, numbers, and adverbs, as well as in the case of verb descriptions. However, in all these contexts, the source is masculinity, from which the feminine derives, so there are two ways: from the most common masculine to feminine.